Biologically Active Compounds from Hops and Prospects for Their Use - Karabín, Marcel; Hudcová, Tereza; Jelínek, Lukáš; Dostálek, Pavel (Comprehensive reviews in food science and food safety, 2016)
Although female cones of the hop plant (Humulus lupulus) are known primarily as raw material supplying characteristic bitterness and aroma to beer, their equally significant health-promoting effects have been known to mankind for several thousand years and hop is a plant traditionally utilized in folk medicine. This paper summarizes the scientific knowledge on the effects of all 3 major groups of secondary metabolites of hops; polyphenols, essential oils, and resins. Because of their chemical diversity, it is no coincidence that these compounds exhibit a wide range of pharmacologically important properties. In addition to antioxidant, anti-inflammatory, and anticancer-related properties, particular attention is being paid to prenylflavonoids that occur almost exclusively in hops and are considered to be some of the most active phytoestrogens known. Hop oils and resins are well known for their sedative and other neuropharmacological properties, but in addition, these compounds exhibit antibacterial and antifungal effects. Recently, alpha bitter acids have been shown to block the development of a number of complex lifestyle diseases that are referred to by the collective name "metabolic syndrome." Information presented in this review confirms the significant potential for the use of hops in the pharmaceutical industry and provides an understanding of beer as a natural drink that, although moderately consumed, may become a source of many health-promoting compounds.
Keywords: polyphenols; bitter acids; hops; biologically active compounds; essential oils